2019
DOI: 10.1007/s10668-019-00511-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional improvement of urban fringe areas: toward achieving sustainable built–natural environment interactions

Abstract: Applying ecological approach in the planning and design of urban fringe areas has gained significant attention in the current decade, and a myriad of research has been conducted using these principals. However, integrating these principles with socioeconomic criteria has been discussed loosely. This could be due to two different realms of thinking which are associated with disciplines of ecology and social-economical sciences making a successful coexistence between these them quite challenging. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The main purposes of development planning indicators are identification and analysis of relevant issues, setting priorities according to objectives, and directing to evaluation of the development plan [50]. Some studies also suggest that there is close association between sustainable development and socio-economic components along with environmental issues [51]. Spatial planners and policy makers at present struggle to comprehend the peri-urban territory, with its blend of land uses and its transitional status between the urban and the provincial [52,53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main purposes of development planning indicators are identification and analysis of relevant issues, setting priorities according to objectives, and directing to evaluation of the development plan [50]. Some studies also suggest that there is close association between sustainable development and socio-economic components along with environmental issues [51]. Spatial planners and policy makers at present struggle to comprehend the peri-urban territory, with its blend of land uses and its transitional status between the urban and the provincial [52,53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, a tendential contraction of agricultural areas has been recorded since the 1960s (Congedo et al, 2017) which testifies how the natural capital of Italy is progressively decreasing, with consequent negative impacts on the quality of environment and landscape (e.g., land degradation, see Salvati et al, 2012;Recanatesi et al, 2016;Imbrenda et al, 2022;Lanfredi et al, 2022;Rodrigo-Comino et al 2022;Nickayin et al, 2022) and in terms of socio-economic disparities (Salvati and Zitti, 2007;Salvati and Zitti, 2009). These impacts generally affect the urban-rural fringe in the world, which is among the most ecologically vulnerable areas due to its peculiarities of transition space (Goodarzi et al, 2019;Coluzzi et al, 2022;Zambon et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Apart from the hydrological benefits of GI‐BMP, these natural‐inspired practices have several socioeconomic, and environmental benefits. Research indicated that GI‐BMP enhances the quality of education (Kevern, 2011), beautifies landscapes (Goodarzi et al, 2019; Saeedi & Darabi, 2019), and reduces the operational and maintain costs of urban landscape (Saeedi & Goodarzi, 2020). Environmentally, GI‐BMP's benefits consists of enhancing water quality (Jia et al, 2012; Urbonas, 2003; York et al, 2015), diminishing air pollution (Jayasooriya et al, 2017; Rafael et al, 2018), and enhancing biodiversity (Capotorti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%